2019
DOI: 10.29333/ojcmt/5930
|View full text |Cite
|
Sign up to set email alerts
|

The Newest Borrowed Words and Methods of their Formation in the Russian- and Chinese-Language Internet Communication Space

Abstract: The article elaborates on a comparative analysis of the methods of borrowing (phonetic, semantic, graphic) foreign words in the modern Russian and Chinese languages. The emphasis is upon the gaming methods of formation of units occurred because of borrowing of foreign language vocabulary within the last 10 years, spread in the Internet but not recorded in any dictionaries, as well as upon the peculiarities of their functioning in the Russian-and Chinese-language Internet communication space. In the research, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Research of functional, semantic and genre characteristics of advertising in terms of stylistics and discourse analysis, peculiarities of construction of advertising text and its semantic and pragmatic organization, use of verbal and non-verbal signs, advertising name, etc. (Dijk van, 1988;Dijk van, 1997;Kara-Murza, 1996;Kryukova, 2004;Kaftandzhiyev, 2005;Vartanova, 2006;Kirpicheva, 2007;Ukhova & Marycheva, 2012;Kalashaova, 2014;Naumova & Budnik, 2014;Aniskina & Ukhova, 2015;Busygina & Zheltukhina, 2015;Boeva-Omelechko et al, 2019;Tameryan et al, 2018a;2018b;2019b;Zhang et al, 2019;Zheltukhina et al, 2019, etc.). It is important to emphasize the fact that previously scientists have not analyzed Chinese medical and cosmetic media advertising in the cognitive and psychological aspect of the media effect on the recipient (Shmeleva, 2018;Volskaya et al, 2018 The hypothesis of the study is that Chinese medical and cosmetic media advertising has a direct effect, revealed in extralinguistic markers, including cognitive and psychological markers, not only on the recipient as a consumer of advertising products and advertising services, but also on Chinese linguoculture, which in turn affects the creation of medical and cosmetic advertising media.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research of functional, semantic and genre characteristics of advertising in terms of stylistics and discourse analysis, peculiarities of construction of advertising text and its semantic and pragmatic organization, use of verbal and non-verbal signs, advertising name, etc. (Dijk van, 1988;Dijk van, 1997;Kara-Murza, 1996;Kryukova, 2004;Kaftandzhiyev, 2005;Vartanova, 2006;Kirpicheva, 2007;Ukhova & Marycheva, 2012;Kalashaova, 2014;Naumova & Budnik, 2014;Aniskina & Ukhova, 2015;Busygina & Zheltukhina, 2015;Boeva-Omelechko et al, 2019;Tameryan et al, 2018a;2018b;2019b;Zhang et al, 2019;Zheltukhina et al, 2019, etc.). It is important to emphasize the fact that previously scientists have not analyzed Chinese medical and cosmetic media advertising in the cognitive and psychological aspect of the media effect on the recipient (Shmeleva, 2018;Volskaya et al, 2018 The hypothesis of the study is that Chinese medical and cosmetic media advertising has a direct effect, revealed in extralinguistic markers, including cognitive and psychological markers, not only on the recipient as a consumer of advertising products and advertising services, but also on Chinese linguoculture, which in turn affects the creation of medical and cosmetic advertising media.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study of neologisms is reflected in the works of such scholars as Katermina (2017), Katermina and Lipiridi (2019), , Ratsiburskaya (2016), Zhang et al (2019) and others. Different articles and monographs connected with the study of neologisms confirm the relevance of this knowledge for modern science.…”
Section: Problem Statementmentioning
confidence: 99%